Safety and Immunogenicity of a 13-valent Pneumococcal Conjugate Vaccine Manufactured With and Without Polysorbate 80 Given to Healthy Infants at 2, 3, 4 and 12 Months of Age. Issue 2 (February 2015) - Gadzinowski, Janusz; Tansey, Susan P.; Wysocki, Jacek; Kopińska, Elzbieta; Majda-Stanisławska, Ewa; Czajka, Hanna; Korbal, Piotr; Pietrzyk, Jacek J.; Baker, Sherryl A.; Giardina, Peter C.; Gruber, William C.; Emini, Emilio A.; et al.
Abstract : Background: Polysorbate 80 (P80), a nonionic detergent used to solubilize proteins, is used in both oral and injectable medications including vaccines. Development studies with 13-valent pneumococcal conjugate vaccine (PCV13) showed that adding P80 resulted in a more robust manufacturing process. Before adding P80 to the formulation of PCV13, we investigated the immunogenicity and safety of PCV13 with and without P80. Methods: Phase 3, parallel-group, randomized, active-controlled, double-blind multicenter trial was conducted at 15 sites in Poland. Healthy infants were randomized (1:1) to receive PCV13+P80 or PCV13 without P80 given at ages 2, 3, 4 and 12 months concomitantly with DTaP-IPV-Hib at 2, 3 and 4 months; hepatitis B at 2 months and measles, mumps, and rubella at 12 months. Serotype-specific antipneumococcal immune responses were evaluated using antipolysaccharide capsular immunoglobulin (Ig)G responses and opsonophagocytic activity (OPA) assay. Safety data were also collected. Results: The 2 treatment groups were demographically similar. Following the infant immunization series, anticapsular IgG antibody geometric mean concentrations and OPA geometric mean titers for each serotype were within 2-fold between the 2 groups. Formal noninferiority criteria for comparison of proportion of responders (subjects with IgG titers ≥0.35 μg/mL) were met for 11 of the 13 serotypes. Overall population responses were highly similar. Anticapsular IgG responses were also within 2-fold following the toddler dose. Safety profiles were similar between the 2 groups. Conclusions: Addition of P80 to PCV13 did not adversely affect PCV13 immunogenicity or safety when compared with vaccine formulated without P80. Abstract : Supplemental Digital Content is available in the text.